Factors affecting Syrian female researchers’ experience during crisis: inductive approach - Dalati, Serene (Business, Management and Economics Engineering, 2021)
Purpose – The purpose of this research is to explore factors influencing Syrian female academic researchers’ experience in academic research in the field of business and economics studies. Research Methodology – The research methodology follows a qualitative approach. The methodology is based on conducting focus groups with female academic researchers selected from Syrian public and private universities, to clarify any potential factors, which may be influencing women researchers’ experience. Subsequently, a semi-structured interview protocol is designed to be applied to this target group. A judgement-sampling technique is selected at Syrian public and private universities. Findings – The research findings indicate that personality traits, passion for research, marital and maternal status are important micro-level factors are influencing female researchers’ experience. Academic work overload, an organisational culture of the institution, need for networking support with the business sector, are identified as meso factors. Finally, social culture and norms of the Middle Eastern societies, stereotyping and interpretation of religion are crucial factors at a macrolevel. The research develops a theoretical framework of dimensions, which may be influencing female academic researchers in the field of business and economics. Research Limitation/Implications – The research limitation is associated with sampling size and geographical scope. Future studies could investigate a larger sample with representative geographical scopes, and employs theory testing approaches. Future research could also extend its investigation to examine further disciplines including science, mathematics, engineering and technology. Practical Implications – The study provides practical advice to decision and policymakers examining employment and hiring structure and suggests evaluating policies associated with support with childcare providing on-campus childcare. The study advises introducing support mechanisms for improving the reward system and compensations schemes for academic researchers, encouraging the development and production of scientific research. Originality/Value – There is no prior research on women researchers in Syria. This research is considered as a new perspective of women researchers in Syria during a sensitive time, which characterises Syria. The study provides a theoretical contribution associated with experiences of female researchers at faculties of business and economics in Syrian higher education.